PERFECTIONISM: RESOURCE OF PATHOLOGY - Jokste, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The main trait differing perfectionists from other individuals is high standards, which is the unifying feature in all models. No matter how well the theories and models of perfectionism are developed, there has always been disagreement about the nature of perfectionism – is it 'The Good, the Bad or the Ugly?' The paper aims to review the studies focused on the mechanisms behind perfectionistic representation, its threats to psychological wellbeing, caused by its pathological side, and look into perfectionism as a possible resource for personal growth and achievement. In the first section of the paper, the aetiology of perfectionism is viewed to see if the foundations add to the type of perfectionism formed. In the second section, models of perfectionism are discussed to see their ability to distinguish between adaptive and maladaptive perfections. Finally, in the third section, perfectionism's positive and negative sides are discussed to understand when perfectionism becomes pathological and when it can be viewed as a resource. In the research of perfectionism, the quantitative approach is mostly used. However, the literature review provides the possibility to have an overview of current knowledge on the nature of perfectionism and to identify gaps in the existing research. The results show that although perfectionism may be viewed both as a positive and negative trait, its negative consequences prevail over its possible positive outcomes. Complex research involving several perfectionism measurements is needed to understand the impact of different combinations of perfectionism types on positive and negative outcomes. The findings of the literature review will serve as the theoretical background for studying perfectionism, its pathological traits, and its possible contribution to achievement.